Photocuring modified graphite felt for vanadium battery and preparation method of photocuring modified graphite felt

By sticking carbon nanomaterials evenly on the graphite felt and introducing cage -type polymer semi -silicon alkane groups, the problem of insufficient existing graphite percent electrical conductivity and reactive activity site, significantly improved the total liquid flow battery Voltage and energy efficiency.

CN119332500AInactive Publication Date: 2025-01-21HANGZHOU DEHAI AIKE ENERGY TECH CO LTD

Patent Information

Application Number
CN202411834689.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing graphite felt is insufficient during the preparation process, resulting in low voltage and energy efficiency of all vanadium flow batteries.

Method used

Through the optical curing process, the carbon nanoma is evenly adhered to the surface of the graphite felt fiber, and the cage type polymer semi -silicon alkane group is introduced to increase the reaction active site.

Benefits of technology

The conductivity and reactive sites of the graphite felt are improved, and the voltage efficiency and energy efficiency of the all-vanadium redox flow battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332500A_ABST
    Figure CN119332500A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of all-vanadium redox flow battery electrodes, and discloses a photocuring modified graphite felt for a vanadium battery and a preparation method thereof.The preparation method comprises the following steps that functional hyperbranched polyethylene containing silicon-oxygen bonds and double bonds is subjected to auxiliary stripping under the action of ultrasound, and graphite and multi-walled carbon nanotubes are modified in situ at the same time; the preparation method comprises the following steps: preparing a high-concentration carbon nanomaterial dispersion liquid, soaking a graphite felt in the carbon nanomaterial dispersion liquid, adding a photoinitiator, stirring and standing, initiating a double-bond reaction through ultraviolet light irradiation to prepare a cured graphite felt, and further calcining to obtain the modified graphite felt. The carbon nanomaterial is uniformly and firmly adsorbed on the fiber surface of the graphite felt, the conductivity of the graphite felt is increased, meanwhile, a cage type polysilsesquioxane group is introduced, the group contains rich silicon-oxygen bonds, and more reaction active sites are provided, so that the voltage efficiency and the energy efficiency of the all-vanadium redox flow battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of all-vanadium liquid flow battery electrodes, and in particular relates to a light-cured modified graphite felt for vanadium batteries and a preparation method thereof. Background Art

[0002] In order to cope with the volatility and intermittency of renewable energy during the day and even between seasons, a new type of long-term distributed energy storage system represented by all-vanadium liquid flow batteries has gradually developed to cope with the impact of volatility and intermittency on the power grid and realize the effective use of renewable energy. Compared with other liquid flow batteries, all-vanadium liquid flow batteries use a single vanadium element as the active material, which can effectively avoid cross-contamination of active ions in the positive and negative electrodes and realize the recycling of electrolytes, making it one of the fastest-growing liquid flow batteries.

[0003] All-vanadium flow batteries are mainly composed of four key materials: electrolyte, proton exchange membrane, bipolar plate and electrode. During operation, the electrolyte flows through the electrode through the pump body, and a redox reaction occurs to achieve the purpose of charging and discharging. As the main place for redox reaction, the electrode needs to have three functions: i. Chemical corrosion resistance; ii. Excellent electrical conductivity; iii. More redox sites. Graphite felt can better meet the above requirements, so it has become one of the ideal materials for electrodes. However, in the process of preparing graphite felt, high temperature is usually used under the protection of inert gas to achieve graphitization of the fiber surface in the felt, which will cause the graphite felt surface to have fewer active functional groups, that is, redox reaction active sites, resulting in low voltage efficiency and energy efficiency of all-vanadium flow batteries. However, insufficient graphitization will affect the conductivity of the electrode and also cause poor performance of the battery. Therefore, for the existing graphite felt, developing a modification method that can increase the redox active sites and improve the conductivity has become a problem that needs to be solved at present. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned prior art, the present invention provides a photocurable modified graphite felt for vanadium batteries and a preparation method thereof. Through the photocuring process, carbon nanomaterials are evenly adhered to the surface of graphite felt fibers to improve conductivity. At the same time, cage-type polysilsesquioxane groups are introduced to increase the reaction active sites by virtue of their abundant silicon-oxygen bonds.

[0005] The present invention adopts the following technical solution: A method for preparing a light-cured modified graphite felt for a vanadium battery comprises at least the following steps: Step S1: under the protection of ethylene atmosphere, 3-10 parts by weight of acrylate monomer, 2-8 parts by weight of cage-type polysilsesquioxane monomer, and 25-50 parts by weight of anhydrous solvent are added to a dry reaction bottle; 0.5 parts by weight of palladium-diimide catalyst is taken, and dissolved in 25-50 parts by weight of anhydrous solvent under the protection of nitrogen to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, the ethylene pressure is adjusted to 0.1-1 MPa, and the reaction is stirred at 25° C. and reacted for 12-48 hours under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a precipitate, and the precipitate is placed in a vacuum drying oven at 40-60° C. and dried for 48-96 hours to obtain a functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds; Step S2: 15 to 50 parts by mass of graphite, 15 to 50 parts by mass of multi-walled carbon nanotubes, and 15 to 100 parts by mass of functionalized hyperbranched polyethylene are sequentially added to 10,000 to 20,000 parts by mass of a solvent, and ultrasonicated for 24 to 96 hours to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, and then centrifuged to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, and a solvent is added to redisperse by ultrasonication to obtain a high-concentration carbon nanomaterial dispersion; Step S3: soaking the graphite felt in a high-concentration carbon nanomaterial dispersion, adding 10 to 20 parts by mass of 2,2-dimethoxy-2-phenylacetophenone, stirring for 2 hours, standing for 2 to 6 hours, then taking out the graphite felt, vacuum drying at 40° C. for 2 hours, and after drying, irradiating with ultraviolet light for 20 minutes to obtain a cured graphite felt; Step S4: placing the solidified graphite felt in a muffle furnace and calcining it at high temperature to obtain modified graphite felt after the calcination.

[0006] Preferably, the acrylate monomer in step S1 includes at least one of 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol diacrylate and triethylene glycol diacrylate.

[0007] Preferably, the cage polysilsesquioxane monomer in step S1 includes at least one of acrylamide isobutyl silsesquioxane and methacryl cage polysilsesquioxane.

[0008] Preferably, the anhydrous solvent in step S1 includes dichloromethane, chloroform, toluene, or chlorobenzene.

[0009] Preferably, the solvent in step S2 includes at least one of chloroform and tetrahydrofuran.

[0010] Preferably, the concentration of the high-concentration carbon nanomaterial dispersion in step S2 is 10-20 mg / mL.

[0011] Preferably, the ultrasonic power in step S2 is 150-300W.

[0012] Preferably, in step S3, the wavelength of the ultraviolet light is 365 nm, and the power of the light emitting machine is 3 kW.

[0013] Preferably, the method of high temperature calcination in step S4 is: placing the cured graphite felt in a muffle furnace, heating the temperature to 400°C at a rate of 20°C / min, maintaining the temperature for 1 to 4 hours, and naturally cooling to room temperature after the calcination is completed.

[0014] A photocurable modified graphite felt for vanadium battery is prepared by adopting the preparation method of the photocurable modified graphite felt for vanadium battery.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention synthesizes functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds, and assists in exfoliation to obtain graphene and oligo-walled carbon nanotubes. The functionalized hyperbranched polyethylene has CH-π interaction with nano-carbon materials and can be adsorbed on the surface of carbon nano-materials to form steric hindrance, prevent carbon nano-materials from agglomerating, improve the dispersibility of carbon nano-materials in graphite felt and the conductivity of graphite felt, and increase the voltage efficiency and energy efficiency of all-vanadium liquid flow batteries.

[0016] 2. The functionalized hyperbranched polyethylene synthesized in the present invention contains double bonds at the end, which can make the carbon nanomaterials evenly and firmly adsorbed on the surface of graphite felt fibers through UV curing and high-temperature calcination, thereby improving the conductivity of the graphite felt and increasing the voltage efficiency and energy efficiency of the all-vanadium liquid flow battery.

[0017] 3. The functionalized hyperbranched polyethylene introduced in the present invention contains cage-type polysilsesquioxane groups, which contain abundant silicon-oxygen bonds, providing more reactive sites and increasing the voltage efficiency and energy efficiency of the all-vanadium liquid flow battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the resistivity of the modified graphite felt prepared in Examples 1 and 2 of the present invention and Comparative Examples 3 and 4; Figure 2 This is a scanning electron microscope image of the modified graphite felt prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0020] Example 1: The following scheme is used to obtain Step S1: under the protection of ethylene atmosphere, 4g of 1,4-butanediol diacrylate monomer, 5g of acrylamide isobutyl silsesquioxane monomer, and 40g of anhydrous dichloromethane are added to a dry reaction bottle; 0.5g of palladium-diimine catalyst is taken, and under the protection of nitrogen, it is dissolved in 25g of anhydrous dichloromethane to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, the ethylene pressure is adjusted to 0.1MPa, and the mixture is stirred at 25°C and reacted for 24h under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a preliminary product after dissolution and precipitation, and the preliminary product is placed in a 60°C vacuum drying oven and dried for 48h to obtain a functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds.

[0021] Step S2: 300 mg of graphite, 300 mg of multi-walled carbon nanotubes, and 600 mg of functionalized hyperbranched polyethylene are added to 150 g of chloroform in sequence, and ultrasonicated for 48 hours at an ultrasonic power of 200 W to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, followed by centrifugation to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, chloroform is added, and re-dispersed by ultrasound to obtain a carbon nanomaterial dispersion with a concentration of 15 mg / mL.

[0022] Step S3: soak the graphite felt in the carbon nanomaterial dispersion, add 15 g of 2,2-dimethoxy-2-phenylacetophenone, stir for 2 hours, let stand for 2 hours, then take out the graphite felt, vacuum dry it at 40°C for 2 hours, and after drying, use 3kW ultraviolet light to irradiate for 20 minutes to obtain cured graphite felt.

[0023] Step S4: placing the cured graphite felt in a muffle furnace, heating the temperature to 400° C. at a heating rate of 20° C. / min, and maintaining the temperature for 2 hours. After the calcination is completed, naturally cooling to room temperature to obtain modified graphite felt.

[0024] Figure 2 This is a scanning electron microscope image of the modified graphite felt in this embodiment. It can be observed that carbon nanomaterials are adhered to the surface of the graphite felt fibers.

[0025] Example 2: Using the following scheme to obtain Step S1: under the protection of ethylene atmosphere, 8g of 1,6-hexanediol diacrylate monomer, 8g of acrylamide isobutyl silsesquioxane monomer, and 50g of anhydrous dichloromethane are added to a dry reaction bottle; 0.5g of palladium-diimine catalyst is taken, and dissolved in 40g of anhydrous dichloromethane under the protection of nitrogen to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, the ethylene pressure is adjusted to 0.1MPa, and the mixture is stirred at 25°C and reacted for 48h under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a preliminary product after dissolution and precipitation, and the preliminary product is placed in a 40°C vacuum drying oven and dried for 72h to obtain a functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds.

[0026] Step S2: 500 mg of graphite, 500 mg of multi-walled carbon nanotubes, and 1 g of functionalized hyperbranched polyethylene are added to 200 g of chloroform in sequence, and ultrasonicated for 72 h at an ultrasonic power of 300 W to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, followed by centrifugation to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, chloroform is added, and re-dispersed by ultrasound to obtain a carbon nanomaterial dispersion with a concentration of 20 mg / mL.

[0027] Step S3: soak the graphite felt in the carbon nanomaterial dispersion, add 20 g of 2,2-dimethoxy-2-phenylacetophenone, stir for 2 hours, let stand for 6 hours, then take out the graphite felt, vacuum dry it at 40°C for 2 hours, and after drying, use 3kW ultraviolet light to irradiate for 20 minutes to obtain cured graphite felt.

[0028] Step S4: placing the cured graphite felt in a muffle furnace, heating the temperature to 400° C. at a heating rate of 20° C. / min, and maintaining the temperature for 4 hours. After the calcination is completed, naturally cooling to room temperature to obtain modified graphite felt.

[0029] Example 3: Using the following scheme to obtain Step S1: under the protection of ethylene atmosphere, 3g of ethylene glycol diacrylate monomer, 2g of methyl methacrylate cage-type silsesquioxane monomer, and 25g of anhydrous chloroform are added to a dry reaction bottle; 0.5g of palladium-diimine catalyst is taken, and it is dissolved in 25g of anhydrous chloroform under the protection of nitrogen to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, the ethylene pressure is adjusted to 1MPa, and the reaction is stirred at 25°C and reacted for 12h under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a preliminary product after dissolution and precipitation, and the preliminary product is placed in a 50°C vacuum drying oven and dried for 96h to obtain a functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds.

[0030] Step S2: 150 mg of graphite, 150 mg of multi-walled carbon nanotubes, and 150 mg of functionalized hyperbranched polyethylene are added to 100 g of chloroform in sequence, and ultrasonicated for 96 hours at an ultrasonic power of 150 W to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, followed by centrifugation to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, chloroform is added, and re-dispersed by ultrasound to obtain a carbon nanomaterial dispersion with a concentration of 10 mg / mL.

[0031] Step S3: soak the graphite felt in the carbon nanomaterial dispersion, add 10 g of 2,2-dimethoxy-2-phenylacetophenone, stir for 2 hours, let stand for 2 hours, then take out the graphite felt, vacuum dry it at 40°C for 2 hours, and after drying, use 3kW ultraviolet light to irradiate for 20 minutes to obtain cured graphite felt.

[0032] Step S4: placing the cured graphite felt in a muffle furnace, heating the temperature to 400° C. at a heating rate of 20° C. / min, and maintaining the temperature for 1 hour. After the calcination is completed, naturally cooling to room temperature to obtain modified graphite felt.

[0033] Example 4: Using the following scheme to obtain Step S1: under the protection of ethylene atmosphere, 10g of triethylene glycol diacrylate monomer, 5g of methyl propylene cage silsesquioxane monomer, and 50g of anhydrous toluene are added to a dry reaction bottle; 0.5g of palladium-diimine catalyst is taken, and it is dissolved in 30g of anhydrous toluene under the protection of nitrogen to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, and the ethylene pressure is adjusted to 0.5MPa, and the reaction is stirred at 25°C and reacted for 24h under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a preliminary product after dissolution and precipitation, and the preliminary product is placed in a 60°C vacuum drying oven and dried for 48h to obtain a functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds.

[0034] Step S2: 300 mg of graphite, 300 mg of multi-walled carbon nanotubes, and 600 mg of functionalized hyperbranched polyethylene are added to 200 g of tetrahydrofuran in sequence, and ultrasonicated for 48 hours at an ultrasonic power of 200 W to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, followed by centrifugation to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, tetrahydrofuran is added, and re-dispersed by ultrasound to obtain a carbon nanomaterial dispersion with a concentration of 20 mg / mL.

[0035] Step S3: soak the graphite felt in the carbon nanomaterial dispersion, add 15 g of 2,2-dimethoxy-2-phenylacetophenone, stir for 2 hours, let stand for 4 hours, then take out the graphite felt, vacuum dry it at 40°C for 2 hours, and after drying, use 3kW ultraviolet light irradiation for 20 minutes to obtain cured graphite felt.

[0036] Step S4: placing the cured graphite felt in a muffle furnace, heating the temperature to 400° C. at a heating rate of 20° C. / min, and maintaining the temperature for 2 hours. After the calcination is completed, naturally cooling to room temperature to obtain modified graphite felt.

[0037] Example 5: Using the following scheme to obtain Step S1: under the protection of ethylene atmosphere, 4g of 1,4-butanediol diacrylate monomer, 5g of acrylamide isobutyl silsesquioxane monomer, and 50g of anhydrous chlorobenzene are added to a dry reaction bottle; 0.5g of palladium-diimine catalyst is taken, and dissolved in 30g of anhydrous chlorobenzene under the protection of nitrogen to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, the ethylene pressure is adjusted to 0.1MPa, and the mixture is stirred at 25°C and reacted for 24h under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a preliminary product after dissolution and precipitation, and the preliminary product is placed in a 60°C vacuum drying oven and dried for 48h to obtain a functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds.

[0038] Step S2: 300 mg of graphite, 300 mg of multi-walled carbon nanotubes, and 300 mg of functionalized hyperbranched polyethylene are added to 100 g of chloroform in sequence, and ultrasonicated for 48 hours at an ultrasonic power of 200 W to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, followed by centrifugation to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, tetrahydrofuran is added, and re-dispersed by ultrasound to obtain a carbon nanomaterial dispersion with a concentration of 20 mg / mL.

[0039] Step S3: soak the graphite felt in the carbon nanomaterial dispersion, add 20 g of 2,2-dimethoxy-2-phenylacetophenone, stir for 2 h, let stand for 4 h, then take out the graphite felt, vacuum dry it at 40 ° C for 2 h, and after drying, use 3 kW ultraviolet light irradiation for 20 min to obtain cured graphite felt.

[0040] Step S4: placing the cured graphite felt in a muffle furnace, heating the temperature to 400° C. at a heating rate of 20° C. / min, and maintaining the temperature for 2 hours. After the calcination is completed, naturally cooling to room temperature to obtain modified graphite felt.

[0041] Comparative Example 1: The following solution is used to obtain Step S1: under the protection of ethylene atmosphere, 4g of 1,4-butanediol diacrylate monomer and 40g of anhydrous dichloromethane are added to a dry reaction bottle; 0.5g of palladium-diimine catalyst is taken, and under the protection of nitrogen, it is dissolved in 25g of anhydrous dichloromethane to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, the ethylene pressure is adjusted to 0.1MPa, and the reaction is stirred at 25°C and reacted for 24h under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a preliminary product after dissolution and precipitation, and the preliminary product is placed in a 60°C vacuum drying oven and dried for 48h to obtain a functionalized hyperbranched polyethylene containing double bonds.

[0042] Step S2: 300 mg of graphite, 300 mg of multi-walled carbon nanotubes, and 600 mg of functionalized hyperbranched polyethylene are added to 150 g of chloroform in sequence, and ultrasonicated for 48 hours at an ultrasonic power of 200 W to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, followed by centrifugation to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, chloroform is added, and re-dispersed by ultrasound to obtain a carbon nanomaterial dispersion with a concentration of 15 mg / mL.

[0043] Step S3: soak the graphite felt in the carbon nanomaterial dispersion, add 15 g of 2,2-dimethoxy-2-phenylacetophenone, stir for 2 hours, let stand for 2 hours, then take out the graphite felt, vacuum dry it at 40°C for 2 hours, and after drying, use 3kW ultraviolet light to irradiate for 20 minutes to obtain cured graphite felt.

[0044] Step S4: placing the cured graphite felt in a muffle furnace, heating the temperature to 400° C. at a heating rate of 20° C. / min, and maintaining the temperature for 2 hours. After the calcination is completed, naturally cooling to room temperature to obtain modified graphite felt.

[0045] Comparative Example 2: The following solution is used to obtain Step S1: under the protection of ethylene atmosphere, 5g of acrylamide isobutyl silsesquioxane monomer and 40g of anhydrous dichloromethane are added to a dry reaction bottle; 0.5g of palladium-diimine catalyst is taken, and under the protection of nitrogen, it is dissolved in 25g of anhydrous dichloromethane to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, the ethylene pressure is adjusted to 0.1MPa, and the reaction is stirred at 25°C and reacted for 24h under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a preliminary product after dissolution and precipitation, and the preliminary product is placed in a 60°C vacuum drying oven and dried for 48h to obtain a functionalized hyperbranched polyethylene containing silicon oxygen bonds.

[0046] Step S2: 300 mg of graphite, 300 mg of multi-walled carbon nanotubes, and 600 mg of functionalized hyperbranched polyethylene are added to 150 g of chloroform in sequence, and ultrasonicated for 48 hours at an ultrasonic power of 200 W to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, followed by centrifugation to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, chloroform is added, and re-dispersed by ultrasound to obtain a carbon nanomaterial dispersion with a concentration of 15 mg / mL.

[0047] Step S3: soaking the graphite felt in the carbon nanomaterial dispersion, stirring for 2 hours, standing for 2 hours, then taking out the graphite felt, and vacuum drying it at 40° C. for 2 hours to obtain cured graphite felt after drying.

[0048] Step S4: placing the cured graphite felt in a muffle furnace, heating the temperature to 400° C. at a heating rate of 20° C. / min, and maintaining the temperature for 2 hours. After the calcination is completed, naturally cooling to room temperature to obtain modified graphite felt.

[0049] Comparative Example 3: The following solution is used to obtain Step S1: 300 mg of graphite and 300 mg of multi-walled carbon nanotubes are added to 150 g of chloroform in sequence, and ultrasonicated for 48 hours at an ultrasonic power of 200 W to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, followed by centrifugation to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, chloroform is added, and re-dispersed by ultrasound to obtain a carbon nanomaterial dispersion with a concentration of 15 mg / mL.

[0050] Step S2: soaking the graphite felt in the carbon nanomaterial dispersion, stirring for 2 hours, standing for 2 hours, then taking out the graphite felt, and vacuum drying at 40° C. for 2 hours to obtain cured graphite felt after drying.

[0051] Step S3: placing the cured graphite felt in a muffle furnace, heating the temperature to 400° C. at a heating rate of 20° C. / min, and maintaining the temperature for 2 hours. After the calcination is completed, naturally cooling to room temperature to obtain modified graphite felt.

[0052] Comparative Example 4: The following solution is used to obtain Blank graphite felt.

[0053] Resistivity test method: The test was performed using a Suzhou Jingge Electronics ST2258C digital four-probe tester. The graphite felt was cut into a size of 10 cm × 5 cm. The resistivity test was performed on 9 fixed positions. The average value was taken to obtain the resistivity of Comparative Examples 3 and 4 and Examples 1 and 2.

[0054] Battery test method: The graphite felts obtained in Examples 1-5 and Comparative Examples 1-4 were assembled into a battery stack for battery performance testing, and the coulombic efficiency, voltage efficiency and energy efficiency were recorded under the same test conditions. The test results are shown in Table 1: Table 1 Battery performance test table of battery stacks assembled using graphite felt from examples and comparative examples

[0055] As shown in Table 1, compared with Comparative Example 4, Examples 1 to 5 have higher voltage efficiency, energy efficiency and capacity retention rate, indicating that the present invention introduces firmly adhered carbon nanomaterials and cage-type polysilsesquioxane groups rich in silicon-oxygen bonds, which can effectively increase the conductivity and reactive sites of the graphite felt electrode, thereby improving the performance of the all-vanadium liquid flow battery; compared with Comparative Example 3, Examples 1 to 5 synthesize functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds, which can assist in the exfoliation of graphene and oligo-walled carbon nanotubes while in-situ adsorbing on their surfaces through CH-π forces to complete functional modification, form steric hindrance, prevent carbon nanomaterials from reaggregating, improve the dispersibility of carbon nanomaterials in graphite felt, and reduce the resistivity of graphite felt, such as Figure 1 As shown, the resistivity of Examples 1 and 2 is reduced by 6.3 mΩ·cm and 7.8 mΩ·cm respectively compared with Comparative Example 3, thereby improving the voltage efficiency and energy efficiency of the battery. In addition, since the functionalized hyperbranched polyethylene terminal contains double bonds, the carbon nanomaterial can be uniformly and firmly adsorbed on the surface of the graphite felt fiber, thereby preventing the carbon nanomaterial from being washed away during the electrolyte circulation process, thereby achieving a good capacity retention rate. Compared with Comparative Example 2, Examples 1 to 5 of the present invention have a higher capacity retention rate, which further proves that the double bonds contained at the end of the functionalized hyperbranched polyethylene bonds, which can be cross-linked and cured by ultraviolet irradiation reaction under the initiation of a photoinitiator to form a stable cross-linked network, so that the carbon nanomaterial can be firmly adsorbed on the graphite felt; in Comparative Example 1, the functionalized hyperbranched polyethylene has double bonds, and the carbon nanomaterial is firmly adsorbed, so it has a capacity retention rate similar to that of Examples 1 to 5, but the functionalized hyperbranched polyethylene in Examples 1 to 5 contains cage-type polysilsesquioxane groups, which contain abundant silicon-oxygen bonds, providing more reactive sites, thereby achieving the purpose of improving the voltage efficiency and energy efficiency of the all-vanadium liquid flow battery.

[0056] From the above detailed description of the embodiments of the present invention, it can be understood that the present invention provides a photocurable modified graphite felt for vanadium batteries and a preparation method thereof. Through the photocuring process, the carbon nanomaterial is evenly and firmly adhered to the surface of the graphite felt fiber to increase the conductivity. At the same time, the cage-type polysilsesquioxane group is introduced. With the help of its rich silicon-oxygen bonds, the reaction active sites are increased, and the conductivity and reaction active sites are simultaneously improved, thereby further improving the voltage efficiency and energy efficiency of the battery.

[0057] Although the preferred implementation of the present invention has been disclosed as above, it does not limit the present invention. Any technician in this field can make appropriate improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims.

Claims

1. A method for preparing light-cured modified graphite felt for vanadium batteries, characterized in that: At least the following steps are included: Step S1: under the protection of ethylene atmosphere, 3-10 parts by weight of acrylate monomer, 2-8 parts by weight of cage-type polysilsesquioxane monomer, and 25-50 parts by weight of anhydrous solvent are added to a dry reaction bottle; 0.5 parts by weight of palladium-diimide catalyst is taken, and dissolved in 25-50 parts by weight of anhydrous solvent under the protection of nitrogen to obtain a catalyst solution, and then under the protection of ethylene atmosphere, the catalyst solution is transferred to the reaction bottle to obtain a reaction liquid, the ethylene pressure is adjusted to 0.1-1 MPa, and the reaction is stirred at 25° C. and reacted for 12-48 hours under light-shielding conditions; after the reaction is completed, the ethylene is stopped, and the reaction liquid is poured into methanol to obtain a precipitate, and the precipitate is placed in a vacuum drying oven at 40-60° C. and dried for 48-96 hours to obtain a functionalized hyperbranched polyethylene containing silicon-oxygen bonds and double bonds; Step S2: 15 to 50 parts by mass of graphite, 15 to 50 parts by mass of multi-walled carbon nanotubes, and 15 to 100 parts by mass of functionalized hyperbranched polyethylene are sequentially added to 10,000 to 20,000 parts by mass of a solvent, and ultrasonicated for 24 to 96 hours to obtain a dispersion containing graphene and oligo-walled carbon nanotubes, and then centrifuged to remove the supernatant to obtain a mixed precipitate containing graphene and oligo-walled carbon nanotube solids, and a solvent is added to redisperse by ultrasonication to obtain a high-concentration carbon nanomaterial dispersion; Step S3: soaking the graphite felt in a high-concentration carbon nanomaterial dispersion, adding 10 to 20 parts by mass of 2,2-dimethoxy-2-phenylacetophenone, stirring for 2 hours, standing for 2 to 6 hours, then taking out the graphite felt, vacuum drying at 40° C. for 2 hours, and after drying, irradiating with ultraviolet light for 20 minutes to obtain a cured graphite felt; Step S4: placing the solidified graphite felt in a muffle furnace and calcining it at high temperature to obtain modified graphite felt after the calcination.

2. The method for preparing a photocurable modified graphite felt for vanadium battery according to claim 1, characterized in that: In step S1, the acrylate monomer includes at least one of 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol diacrylate, and triethylene glycol diacrylate.

3. The method for preparing a photocurable modified graphite felt for vanadium battery according to claim 1, characterized in that: In step S1, the cage polysilsesquioxane monomer includes at least one of acrylamide isobutyl silsesquioxane and methacrylic cage polysilsesquioxane.

4. The method for preparing a photocurable modified graphite felt for vanadium battery according to claim 1, characterized in that: The anhydrous solvent in step S1 includes dichloromethane, chloroform, toluene, and chlorobenzene.

5. The method for preparing a light-cured modified graphite felt for vanadium batteries according to claim 1, characterized in that: In step S2, the solvent includes at least one of chloroform and tetrahydrofuran.

6. The method for preparing a photocurable modified graphite felt for vanadium battery according to claim 1, characterized in that: The concentration of the high-concentration carbon nanomaterial dispersion in step S2 is 10-20 mg / mL.

7. The method for preparing a light-cured modified graphite felt for vanadium batteries according to claim 1, characterized in that: In step S2, the ultrasonic power is 150-300W.

8. The method for preparing a light-cured modified graphite felt for vanadium batteries according to claim 1, characterized in that: The wavelength of the ultraviolet light in step S3 is 365nm, and the power of the light emitting machine is 3kW.

9. The method for preparing a light-cured modified graphite felt for vanadium batteries according to claim 1, characterized in that: The method of high temperature calcination in step S4 is: placing the cured graphite felt in a muffle furnace, heating the temperature to 400°C at a rate of 20°C / min, maintaining the temperature for 1 to 4 hours, and naturally cooling to room temperature after the calcination is completed.

10. A light-cured modified graphite felt for vanadium batteries, characterized in that: The photocurable modified graphite felt for vanadium battery is prepared by the method for preparing the photocurable modified graphite felt for vanadium battery as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing two-component heat-conducting silicone rubber by taking graphene and multi-walled carbon nanotubes as mixed filler

    CN114854197A

  • Carbon nano composite material modified graphite felt for vanadium battery and preparation method of carbon nano composite material modified graphite felt

    CN115559110A

  • POSS (Polyhedral Oligomeric Silsesquioxane)-based acryloyloxy hyperbranched polyethylene and application of POSS-based acryloyloxy hyperbranched polyethylene in graphene / carbon nanotube hybrid electric heating coating

    CN115850608A

  • Composite proton exchange membrane for all-vanadium redox flow battery and preparation method of composite proton exchange membrane

    CN118930927A

  • Preparation method of functional boron nitride modified PVDF (polyvinylidene fluoride)-based nano-composite dielectric film

    JP2023089954A

Cited By

  • Method for activating surface of graphite felt and removing amorphous carbon by utilizing photothermal effect

    CN120015854A

  • Multi-dimensional conductive material, preparation method thereof and application of multi-dimensional conductive material in all-vanadium redox flow battery

    CN120136092A

  • Catalytic modified graphite felt electrode for vanadium battery and preparation method

    CN120221679A

  • Catalytically modified graphite felt electrode for vanadium battery and preparation method thereof

    CN120221679B